2021
DOI: 10.3390/ani11071947
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and Dietary Effects on Egg Quality of Local Chicken Breeds and Their Crosses Fed with Faba Beans

Abstract: The quality of chicken eggs is an important criterion for food safety and the consumers’ choice at the point of sale. Several studies have shown that egg quality can be influenced by the chickens’ genotype and by the composition of the diet. The present study aimed to evaluate the effect of faba beans as a substitute for soybeans in the diet of chickens originating from traditional low-performance breeds in comparison with high-performing laying type hens and their crosses on egg quality parameters. Chickens o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…In the present study, signi cantly higher HU was observed in round eggs compared to sharp eggs in HEN and this was consistent with Duman et al (2016). This may be related to the larger size (hence higher albumen proportion) of round eggs compared to sharp eggs in this genotype and this agreed with the ndings of previous studies (Leiboldt et al, 2018;Nolte et al, 2021;Rakonjac et al, 2021).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, signi cantly higher HU was observed in round eggs compared to sharp eggs in HEN and this was consistent with Duman et al (2016). This may be related to the larger size (hence higher albumen proportion) of round eggs compared to sharp eggs in this genotype and this agreed with the ndings of previous studies (Leiboldt et al, 2018;Nolte et al, 2021;Rakonjac et al, 2021).…”
Section: Resultssupporting
confidence: 93%
“…The signi cantly improved EW in ginger group could be responsible for the improvement in EL, ESA, and EV observed in this group and this could be attributed to the health promoting effects of ginger probably due to its content of bene cial bioactive compounds (Nemati et 2023) however, reported nonsigni cant effect of ginger on ESI at 8 weeks of lay but signi cant effect at 10 weeks of lay which suggests an age dependent effect. Genotypic differences in YW and YR as were observed in the present study agreed with previous studies (Nolte et al, 2021;Rakonjac et al, 2021;. The higher YW in SB eggs is attributable to the larger egg size however; these eggs had lower YR compared to HEN eggs indicating that selection for higher egg size (egg weight) in hens may not proportionately improve egg yolk content.…”
Section: Resultssupporting
confidence: 90%
“…Crossing with WR therefore considerably improved both laying performance and laying efficiency, with FCR decreasing from 5.6 in LH to 2.9 in LH × WR. The laying curve of LH × WR closely resembled that of NH × Bresse and Bresse × WR, while purebred LH hens started laying later (10% laying performance in week 24 vs. 20-21%), and peaked later (week 29 vs. [23][24][25][26][27] and lower (64.9% vs. 87.6-93.5%) than the other breeds, again underlining the effect of the lack of breeding focus on laying performance in this breed. The concept of crossing an indigenous breed with a layer breed in order to obtain a higher laying performance while providing an incentive to keep the pure breed for genetic diversity is not new, and among other breeds has been shown to be effective in the cross of Vorwerkhuhn × Lohmann layer line [26] and for various crosses of Vorwerkhuhn, Bresse, and White Rock [27].…”
Section: Feed Consumption and Laying Performance Of The Hensmentioning
confidence: 66%
“…Eggshell color is significantly affected by genotypic characteristics. Crossbreeding of layers chicken producing eggs with white eggshell and light brown eggshell have eggs with combined color of the parents [16]. The variation of eggshell color due to crossbreeding is influenced by the additive genes responsible for the characteristics of eggshell color [17].…”
Section: Egg Qualitymentioning
confidence: 99%